PENYULUHAN PENULISAN PENELITIAN TINDAKAN KELAS (PTK) BAGI GURU-GURU SDN TUMPUKRENTENG 01 TUREN MALANG - Nelya Eka Susanti; Akhmad Faruq Hamdani (Dedication : Jurnal Pengabdian Masyarakat, 2018)
Community service activities titled "Counseling Class Action Research (PTK) for teachers of SDN Tumpukrenteng 01 Turen Malang" option to provide knowledge and skills for teachers at SDN Tumpukrenteng 01 Turen Malang on how to compose research titles, introductions, , and research methods on PTK. The knowledge and skills needed through the counseling are expected to improve teacher performance SDN Tumpukrenteng 01 Turen in improving the quality of learning in the classroom through PTK. This devotional activity was held on 21 and 22 August 2017 at SDN Tumpukrenteng 01 Turen Malang with lecture, question and answer method, and independent practice. This devotion activity was positively responded by all participants. This can be seen through the number of teachers present and asking questions during the question and answer session. In addition, teachers are also enthusiastic in presenting various problems in the classroom related to learning. The ability of teachers to find problems and find solutions to these problems has also improved considerably. Teachers have also been able to develop a PTK proposal in accordance with classroom learning conditions.